2017
DOI: 10.1177/0011000017733048
|View full text |Cite
|
Sign up to set email alerts
|

Black Lives Matter: A Call to Action for Counseling Psychology Leaders

Abstract: Police brutality and widespread systemic racism represent historical and current sources of trauma in Black communities. Both the Black Lives Matter movement and counseling psychology propose to confront these realities at multiple levels. Black Lives Matter seeks to increase awareness about systemic racism and promote resilience among Black people. Counseling psychology states values of multiculturalism, social justice, and advocacy. Executive leadership in counseling psychology may seek to promote racial jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 48 publications
0
99
0
Order By: Relevance
“…Psychology does have a role in developing more equitable social and political institutions 53 and through graduate and continuing education, 12 psychologists can make strong contributions to help mend the relationships between the Black community and the criminal justice system. By engaging in research and advocacy, psychologists can provide training to both the Black community and police departments on how violence, cognition, and media impact our mental health and relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychology does have a role in developing more equitable social and political institutions 53 and through graduate and continuing education, 12 psychologists can make strong contributions to help mend the relationships between the Black community and the criminal justice system. By engaging in research and advocacy, psychologists can provide training to both the Black community and police departments on how violence, cognition, and media impact our mental health and relationships.…”
Section: Resultsmentioning
confidence: 99%
“…The field of psychology is a uniquely qualified group of professionals who could and should assist in constructing healthy relationships between the criminal justice system/police departments and Black communities they serve. 12…”
Section: Introductionmentioning
confidence: 99%
“…Intentional leverage of one’s privilege may contribute to greater institutional justices (e.g., recruitment and hiring diverse faculty, educational materials from representative authors, power sharing). Accordingly, Hargons et al (2017) emphasized the importance of listening to leaders who have embodied knowledge of oppression and marginalization.…”
Section: Discussionmentioning
confidence: 99%
“…Remmers, Topolinski, and Koole (2016) found that mindfulness improved both implicit and explicit levels of emotional regulation. Hargons et al (2017) emphasized that emotional considerations are vital for healing, understanding, and antiracism leadership in the counseling field, given the historical and current racial trauma that Black communities experience. Furthermore, Bartoli, Bentley-Edwards, García, Michael, and Ervin (2015) outlined aspects counselors need to understand about race: (a) racism may evoke unpleasant emotions; (b) race is a source of identity; (c) systemic racism is personal; (d) there are costs related to racism; and (e) talking about race with clients has meaning.…”
Section: Multicultural Mindfulnessmentioning
confidence: 99%
“…All school psychologists, regardless of their race and/or ethnicity, should be prepared to serve students and schools in diverse communities; however, the need for racial and ethnic diversity amongst school psychologists is heightened given the current political and social climate in the United States. For example, immigration policies that separate Latinx families seeking refuge in the United States (National Association of School Psychologists [NASP], 2018a); bans on individuals of Muslim faith from entering the country (Sondell, Baggett, & Dunn, ); state‐sanctioned violence against Black people, including police killing of unarmed Black men, women, and youth (Hargons et al, ); and persistent bias and inequities in US public schools (Proctor, ) create the conditions for minoritized students to experience fear, anger, and trauma (NASP, , 2018a; Sondell et al, ) as well as educational outcomes that reinforce the existing economic, ethnic, and racial stratification in the United States (Proctor, ). Proctor and Truscott () noted the necessity of having culturally competent school psychologists of all races, but especially those of color, to offer expertise and services that benefit students across a range of educational, social, and psychological issues inclusive of and beyond special education.…”
Section: Introductionmentioning
confidence: 99%